Investigation of Isoform Specific Functions of the V-ATPase a Subunit During Drosophila Wing Development - Mo, Dongqing; Chen, Yao; Jiang, Na; Shen, Jie; Zhang, Junzheng (Frontiers in Genetics, 2020)
The vacuolar ATPases (V-ATPases) are ATP-dependent proton pumps that play vital roles in eukaryotic cells. Insect V-ATPases are required in nearly all epithelial tissues to regulate a multiplicity of processes including receptor-mediated endocytosis, protein degradation, fluid secretion and neurotransmission. Composed of fourteen different subunits, several V-ATPase subunits exist in distinct isoforms to perform cell type specific functions. The 100kD a subunit (Vha100) of V-ATPases are encoded by a family of five genes in Drosophila, but their assignments are not fully understood. Here we report an experimental survey of the Vha100 gene family during Drosophila wing development. A combination of CRISPR-Cas9 mutagenesis, somatic clonal analysis and in vivo RNAi assays is used to characterize the requirement of Vha100 isoforms, and mutants of Vha100-2, Vha100-3, Vha100-4 and Vha100-5 genes were generated. We show that Vha100-3 and Vha100-5 are dispensable for fly development, while Vha100-1 is not critically required in the wing. As for the other two isoforms, we find that Vha100-2 regulates wing cuticle maturation, while Vha100-4 is the single isoform involved in developmental patterning. More specifically, Vha100-4 is required for proper activation of the Wingless signaling pathway during fly wing development. Interestingly, we also find a specific genetic interaction between Vha100-1 and Vha100-4 during wing development. Our results revealed the distinct roles of Vha100 isoforms during insect wing development, providing a rationale for understanding the diverse roles of V-ATPases.